A highly efficient porous rod-like Ce-doped ZnO photocatalyst for the degradation of dye contaminants in water - Hu, Binjing; Sun, Qiang; Zuo, Chengyi; Pei, Yunxin; Yang, Siwei; Zheng, Hui; Liu, Fangming (Beilstein Journal of Nanotechnology, 2019)
A mild and simple method was developed to synthesize a highly efficient photocatalyst comprised of Ce-doped ZnO rods and optimal synthesis conditions were determined by testing samples with different Ce/ZnO molar ratios calcined at 500 °C for 3 hours via a one-step pyrolysis method. The photocatalytic activity was assessed by the degradation of a common dye pollutant found in wastewater, rhodamine B (RhB), using a sunlight simulator. The results showed that ZnO doped with 3% Ce exhibits the highest RhB degradation rate. To understand the crystal structure, elemental state, surface morphology and chemical composition, the photocatalysts were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM) and inductively coupled plasma emission spectroscopy (ICP), respectively. The newly developed, robust, field-only surface integral method was employed to explore the relationship between the remarkable catalytic effect and the catalyst shape and porous microstructure. The computational results showed that the dipole-like field covers the entire surface of the rod-like Ce-doped ZnO photocatalyst and is present over the entire range of wavelengths considered. The optimum degradation conditions were determined by orthogonal tests and range analysis, including the concentration of RhB and catalyst, pH value and temperature. The results indicate that the pH value is the main influential factor in the photocatalytic degradation process and the optimal experimental conditions to achieve the maximum degradation rate of 97.66% in 2 hours are as follows: concentration (RhB) = 10 mg/L, concentration (catalyst) = 0.7 g/L, pH 9.0 and T = 50 °C. These optimum conditions supply a helpful reference for large-scale wastewater degradation containing the common water contaminant RhB.
Keywords: Ce-doped ZnO; photocatalyst; rhodamine B; solar degradation; surface shape

(untitled) - Vacchi, F. I.; Vendemiatti, J. A. d. S.; da Silva, B. F.; Zanoni, M. V. B.; Umbuzeiro, G. d. A. (Sci. Total Environ., 2017)

(untitled) - Ghaffar, A.; Zhang, L.; Zhu, X.; Chen, B. (Environ. Sci. Technol., 2018)

(untitled) - Gaya, U. I.; Abdullah, A. H. (J. Photochem. Photobiol., C, 2008)

(untitled) - Janoš, P. (Environ. Sci. Technol., 2003)

(untitled) - Pal, B.; Kaur, R.; Grover, I. S. (J. Ind. Eng. Chem. (Amsterdam, Neth.), 2016)

(untitled) - Santhosh, C.; Velmurugan, V.; Jacob, G.; Jeong, S. K.; Grace, A. N.; Bhatnagar, A. (Chem. Eng. J., 2016)

(untitled) - Shaari, N.; Tan, S.; Mohamed, A. (J. Rare Earths, 2012)

(untitled) - Pardeshi, S. K.; Patil, A. B. (J. Mol. Catal. A: Chem., 2009)

(untitled) - Ahmad, M.; Ahmed, E.; Zafar, F.; Khalid, N. R.; Niaz, N. A.; Hafeez, A.; Ikram, M.; Khan, M. A.; Hong, Z. (J. Rare Earths, 2015)

(untitled) - Cerrato, E.; Gionco, C.; Paganini, M. C.; Giamello, E. (J. Phys.: Condens. Matter, 2017)

(untitled) - Samadi, M.; Zirak, M.; Naseri, A.; Khorashadizade, E.; Moshfegh, A. Z. (Thin Solid Films, 2016)

(untitled) - Wang, L.; Ji, Z.; Lin, J.; Li, P. (Mater. Sci. Semicond. Process., 2017)

(untitled) - Paganini, M. C.; Dalmasso, D.; Gionco, C.; Polliotto, V.; Mantilleri, L.; Calza, P. (ChemistrySelect, 2016)

(untitled) - Mahmood, A.; Guo, W.; Tabassum, H.; Zou, R. (Adv. Energy Mater., 2016)

(untitled) - Yang, L.; McNichols, B. W.; Davidson, M.; Schweitzer, B.; Gómez-Gualdrón, D. A.; Trewyn, B. G.; Sellinger, A.; Carreon, M. A. (Catal. Sci. Technol., 2017)

(untitled) - Zhang, T.; Lin, W. (Chem. Soc. Rev., 2014)

(untitled) - Yang, L.; Ruess, G. L.; Carreon, M. A. (Catal. Sci. Technol., 2015)

(untitled) - Miao, Y.; Zhang, H.; Yuan, S.; Jiao, Z.; Zhu, X. (J. Colloid Interface Sci., 2016)

(untitled) - Kolodziejczak-Radzimska, A.; Jesionowski, T. (Materials, 2014)

(untitled) - Lin, J.-C.; Lee, C.-P.; Ho, K.-C. (J. Mater. Chem., 2012)

(untitled) - Koao, L. F.; Dejene, F. B.; Swart, H. C.; Botha, J. R. (J. Lumin., 2013)

(untitled) - Chouchene, B.; Ben Chaabane, T.; Balan, L.; Girot, E.; Mozet, K.; Medjahdi, G.; Schneider, R. (Beilstein J. Nanotechnol., 2016)

(untitled) - Venna, S. R.; Jasinski, J. B.; Carreon, M. A. (J. Am. Chem. Soc., 2010)

(untitled) - Zhu, M.; Jasinski, J. B.; Carreon, M. A. (J. Mater. Chem., 2012)

(untitled) - Chen, Y.-Z.; Zhang, R.; Jiao, L.; Jiang, H.-L. (Coord. Chem. Rev., 2018)

(untitled) - Liang, Y.; Guo, N.; Li, L.; Li, R.; Ji, G.; Gan, S. (RSC Adv., 2015)

(untitled) - Rezaei, M.; Habibi-Yangjeh, A. (Appl. Surf. Sci., 2013)

(untitled) - Faisal, M.; Ismail, A. A.; Ibrahim, A. A.; Bouzid, H.; Al-Sayari, S. A. (Chem. Eng. J., 2013)

(untitled) - Jiang, J.; Zhang, K.; Chen, X.; Zhao, F.; Xie, T.; Wang, D.; Lin, Y. (J. Alloys Compd., 2017)

(untitled) - Chang, C.-J.; Lin, C.-Y.; Chen, J.-K.; Hsu, M.-H. (Ceram. Int., 2014)

(untitled) - Chen, H.; Shen, K.; Chen, J.; Chen, X.; Li, Y. (J. Mater. Chem. A, 2017)

(untitled) - Zammit, I.; Vaiano, V.; Iervolino, G.; Rizzo, L. (RSC Adv., 2018)

(untitled) - Chen, J.; Chen, Y.; Zhou, M.; Huang, Z.; Gao, J.; Ma, Z.; Chen, J.; Tang, X. (Environ. Sci. Technol., 2017)

(untitled) - Zhou, Y.; Hao, C.; Dang, Y.; Chen, S. (J. Electrochem. Soc., 2018)

(untitled) - Mahmoud, W. E. (J. Cryst. Growth, 2010)

(untitled) - Labhane, P. K.; Sonawane, G. H.; Sonawane, S. H. (Green Process. Synth., 2018)

(untitled) - Sun, Q.; Klaseboer, E.; Chan, D. Y. C. (Phys. Rev. B, 2017)

(untitled) - Klaseboer, E.; Sun, Q.; Chan, D. Y. C. (IEEE Trans. Antennas Propag., 2017)

Optical constants - Querry, M. R.

(untitled) - Pan, Y.; Sun, K.; Liu, S.; Cao, X.; Wu, K.; Cheong, W.-C.; Chen, Z.; Wang, Y.; Li, Y.; Liu, Y.; Wang, D.; Peng, Q.; et al. (J. Am. Chem. Soc., 2018)